Vestibular Infant Screening-Rehabilitation (VIS-REHAB): protocol for a randomised controlled trial on Vestibular Rehabilitation Therapy (VRT) in vestibular-impaired children - Ruth Van Hecke; Leen Maes; Ingeborg Dhooge; Marieke Fontaine; Cleo Dhondt; Frederic Acke; Lena Van den Bossche; Helen Van Hoecke; Els De Leenheer (BMJ Open)
Introduction A vestibular deficit can have a substantial impact on the overall development of children. Therefore, it is of utmost importance that vestibular-impaired problems are treated early and effectively through Vestibular Rehabilitation Therapy (VRT). Although VRT is sufficiently proven and standardised in adults, there remains a lack of research examining its efficacy in children. To assess the effectiveness of VRT in vestibular-impaired children, the Vestibular Infant Screening-Rehabilitation (VIS-REHAB) protocol was developed with the following objectives: (1) to investigate the short-term effect of a combined postural control and gaze stabilisation protocol, compared with receiving no therapy and (2) to investigate the most important factors that may influence the effect of and outcome after application of the VIS-REHAB protocol in a group of vestibular-impaired children. This study aims to address lingering questions in the existing literature in a standardised manner, with the ultimate objective to establish evidence-based rehabilitation guidelines.Methods and analysis The VIS-REHAB study is a two-parallel group, superiority, randomised controlled crossover trial with 1:1 allocation ratio. The study includes patients aged 3–17 years old with identified peripheral vestibular dysfunction. Primary and secondary outcome measures assess gaze stability, postural stability, motor performance and quality of life. The effectiveness of the VIS-REHAB protocol will be evaluated through parallel group and crossover analyses using analysis of covariance (ANCOVA). Additionally, prespecified subgroup analyses will be conducted to assess influencing factors that may impact the outcome and effect of VIS-REHAB.Ethics and dissemination At the start of the VIS-REHAB study, an amendment will be submitted to the ethics committee of Ghent University Hospital for the following applications: (EC2018/0435), (EC2018/0959), (EC2015/1441) and (EC2015/1442). The trial is registered at Clinical Trials (clinicaltrials.gov) with registry name VIS-REHAB and identifier NCT06177132. All research findings will be disseminated in peer-reviewed journals.Trial registration number NCT06177132.